Prey density determines the faecal-marking behaviour of a solitary predator, the Iberian lynx (Lynx pardinus). Issue 3 (4th May 2019) - Burgos, Tamara; Virgós, Emilio; Valero, Emma S.; Arenas-Rojas, Rafael; Rodríguez-Siles, Javier; Recio, Mariano R.
Abstract : Scent-marking is a common behaviour among mammals with different functions including territory marking. However, this behaviour has high energy costs and thus a territory owner must select the most strategic sites to place its scent marks. We hypothesised that the scent-marking behaviour of the Iberian lynx ( Lynx pardinus ), an endangered feline and a food specialist, is positively related to the abundance and distribution of its main prey, the European wild rabbit ( Oryctolagus cuniculus ). We predicted that the distribution of rabbits as a staple food resource could determine the patterns of scent-marking by the lynx using communication signals. We selected two areas of Sierra Morena (Andalucia, Spain) with different densities of rabbits. The most intensively used faecal-marking locations by the lynx were those of a high rabbit density ( Χ 2  = 16.54, df = 1, P < 0.0001). Conversely, the lynx marked in other locations not associated with rabbit presence such as crossroads and sheltered locations dominated by shrubs and rocks wherever the rabbit was not a limiting resource and was distributed homogeneously. This behaviour suggests scent-marking might have other alternative functions such as increasing the likelihood of detection or marking key resources.